2022
DOI: 10.1186/s12903-022-02164-8
|View full text |Cite
|
Sign up to set email alerts
|

Bone quality effect on short implants in the edentulous mandible: a finite element study

Abstract: Introduction The aim of this study was to verify whether the use of short implants could optimize stress distribution of bone surrounding implants in atrophic mandibles with different bone qualities. Methods A three-dimensional model of the atrophic mandible with three levels of bone quality was made using computer software. Short implants (6 mm) and standard implants (10 mm) were used in four designs: Design 1 "All-On four", Design 2 "All-On-four"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…Our results demonstrated that significant stress concentration exists in the implant neck region, at the implant-abutment connection. This agrees with the findings in prior research [33,34].…”
Section: Discussionsupporting
confidence: 94%
“…Our results demonstrated that significant stress concentration exists in the implant neck region, at the implant-abutment connection. This agrees with the findings in prior research [33,34].…”
Section: Discussionsupporting
confidence: 94%
“…As seen on the stress distribution maps, noted stress values were peak values denoted at a specific position, however, in reality, these maximum stresses occur as a load transmitted at the bone-implant interface, not at a single point [47]. Although comparisons may be hindered by the different model characteristics set by researchers, our results have yielded similar tensile and compressive values in the same order to other previously published reports assessing stresses on mandibular bone tissue [4,21,36,37,46,[48][49][50]. The mandibular bone adapts to its loading and responds to stresses by bone formation or resorption, i.e., neither unloaded nor overloaded areas are desirable due to long-term consequences [51].…”
Section: Discussionsupporting
confidence: 82%
“…With advances in surgical techniques, implant surface treatment, and the concept of primary stability, the use of short implants has become a viable option for atrophic mandibles 22 , 23 and atrophic maxilla’s 24 . Furthermore, the loss rate for short implants is considered only 20% 25 .…”
Section: Discussionmentioning
confidence: 99%